HISTORICITY AND HUMANITY IN HEYDAR ALIYEV’S LITERARY AND THEORETICAL HERITAGE - Akhmedova, Salatin (Revista Gênero e Interdisciplinaridade, 2020)
An analysis of the history of Azerbaijan’s independent statehood indicates that such a difficult, complex and honorable mission as building a state could be led by a strong-willed person with a broad and global worldview, supported by the people and become their national leader. In the late 90s of the XX century, the only leader who could claim this role in Azerbaijan and was able to cope with this work was Heydar Aliyev. An important part of the theoretical and practical activities of Heydar Aliyev is his doctrine of national statehood, a national-spiritual and ideological-political worldview. The study of its rich heritage in this area deserves to play the role of an example not only for current socio-political circles, but also for future generations, all the leaders who will lead Azerbaijan. The ideological world of this historical figure, laying the solid foundation of modern Azerbaijan, will always illuminate the path of his followers.